2009
DOI: 10.1007/s11664-008-0633-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Drop Performance of Solder Joints by Evaluating the Elastic Strain Energy from High-Speed Ball Pull Tests

Abstract: Despite being expensive and time consuming, board-level drop testing has been widely used to assess the drop or impact resistance of the solder joints in handheld microelectronic devices, such as cellphones and personal digital assistants (PDAs). In this study, a new test method, which is much simpler and quicker, is proposed. The method involves evaluating the elastic strain energy and relating it to the impact resistance of the solder joint by considering the YoungÕs modulus of the bulk solder and the fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…More importantly, compared to their Pb-containing counterparts, these solders have a significantly lower drop resistance, which poses a serious problem for a variety of promising mobile applications. 3,4 This resistance can be improved by increasing the elastic strain energy of the joint during high-speed tensile loading. In other words, the drop resistance can be increased by either reducing the Young's modulus of the solder material or increasing the high-speed fracture strength at the solder joint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, compared to their Pb-containing counterparts, these solders have a significantly lower drop resistance, which poses a serious problem for a variety of promising mobile applications. 3,4 This resistance can be improved by increasing the elastic strain energy of the joint during high-speed tensile loading. In other words, the drop resistance can be increased by either reducing the Young's modulus of the solder material or increasing the high-speed fracture strength at the solder joint.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the drop resistance can be increased by either reducing the Young's modulus of the solder material or increasing the high-speed fracture strength at the solder joint. 4 Furthermore, the wettability, creep strength, and tensile strength of Pb-free solders can be improved by doping the solder joints with small amounts of a rare-earth (RE) element. 5 In the present study, we evaluate a potential drop-resistant Pb-free solder solution by adding small amounts (0.02 wt.% to 0.1 wt.%) of Y to the Sn-1.0Ag-0.5Cu solder.…”
Section: Introductionmentioning
confidence: 99%
“…One common method is mainly concerned with the mechanical properties of ball grid arrays (BGAs) based on actual packaging structures. You et al 4 performed a high-speed pull test on different solder ball joints and obtained the elastic strain energies. They found that the ranking of elastic strain energies was consistent with the board-level drop performance of the solder joints.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid increase in the number of miniaturized consumer electronics which can be easily dropped by the user has resulted in significant interest in the impact response of such interconnects. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Impact reliability tests carried out by dropping the device, either once or a specific number of times, from a chosen height provide a simple means of quantitative joint system evaluation. 16 However, such studies do not provide sufficient information to select solder materials and/or joint geometries for improving the impact reliability of solder interconnects.…”
Section: Introductionmentioning
confidence: 99%
“…These studies impose impact loading on the bonded solder balls, providing results from a better controlled impact loading scenario. [5][6][7][8][9] However, it is still difficult to realize the true nature of impact loading experienced by solder joints present in electronic interconnects from these studies. Solder interconnects are part of a multicomponent system, and the loading realized by the solder region is a consequence of the impact imposed at some other location in the system.…”
Section: Introductionmentioning
confidence: 99%